Exploring Gender Differences in Leadership Aspirations: A Four-Year Longitudinal Study of College Students From Adverse Backgrounds - Gregory C. Wolniak; Emily C. Chen-Bendle; Jennifer L. Tackett (SAGE Publishing, 2023)
The gender disparity in leadership positions is substantial and critical yet persists despite decades of focused study. Critical developmental periods, such as emerging adulthood, may be particularly relevant to attend to if we hope to find effective interventions to tackle this problem. The present study draws on longitudinal data covering four years of college among a socio-demographically and nationally diverse sample of college students with adverse backgrounds (N = 404) who enrolled at one of 182 four-year colleges or universities across the United States. Results indicate that female students enter college with significantly lower levels of leadership aspirations than their male counterparts. Once in college, despite greater likelihoods of participating in activities conceptualized as "leadership learning experiences," female disadvantages persist. Overall, development experiences over four years of college had no discernable effect on gender disparities in leadership aspirations. Implications for research and practice are discussed.